THE MAZE OF THE NEW WORLD ORDER AND ARAB IDENTITIES BETWEEN EXTREMISM AND VIOLENCE - Wail Zaoui (International Journal of Innovative Technologies in Social Science, 2025)
This study explores the challenges faced by first-year English as a Foreign Language (EFL) students at El-Bayadh University in developing their oral communication skills. It identifies key obstacles such as limited vocabulary, lack of confidence, fear of making mistakes, and insufficient exposure to authentic language use. Additionally, cultural and educational factors, including traditional teaching methods and limited practical language use, contribute to these challenges. The study also examines strategies to overcome these barriers, such as increasing interactive classroom activities, promoting peer communication, and boosting self-confidence through positive reinforcement. By identifying these obstacles and suggesting effective strategies, the research aims to offer insights that could enhance the oral communication proficiency of EFL students, fostering more effective language learning in university settings.